The Effect of Customer Satisfaction on Customer Loyalty in Kartu As Products in Makassar City - Muhammad Ilham Wardhana Haeruddin; Muhammad Ikhwan Maulana Haeruddin (Jurnal Ad'ministrare, 2020)
This study aims to determine the influence of customer satisfaction on customer loyalty in Kartu As products in Makassar City. This research was conducted in Makassar City with 105 respondents. The sampling technique used stratified random sampling. This study was analyzed using hypothesis testing with multiple regression analysis with the help of the SPSS 21 computer program, to perform the f-test, t-test, and the calculation of R square (r2). The results of the analysis show that simultaneously the X variable (overall customer satisfaction, customer satisfaction dimensions, confirmation of expectations, re-purchase interest, willingness to recommend and customer dissatisfaction) has a significant effect on customer loyalty. In the t-test, there are two subvariables X that are not significant because the value of t count <t table, namely the dimensions of customer satisfaction (X2), and willingness to recommend (X5). From the calculation of R square (r2) of 0.423, it shows that the percentage of the influence of variable X on variable Y is 42.3%.